Protocol for fully digital and customized management of concomitant temporomandibular joint replacement and orthognathic surgery. Issue 2 (February 2021) - Sembronio, S.; Tel, A.; Robiony, M.
Abstract: End-stage temporomandibular joint (TMJ) disease is caused by a multitude of pathological processes that impair TMJ anatomy and function. In many cases, end-stage TMJ disease and dentofacial skeletal deformities coexist. The optimal treatment for such conditions is total alloplastic joint replacement and orthognathic surgery. Such procedures have historically been conducted in two separate stages. Furthermore, while technological improvements resulting from the widespread adoption of virtual reality initially led to significant improvements in the field of orthognathic planning, the adoption of virtual design techniques to optimize TMJ reconstruction was a later achievement. Therefore, planning for TMJ replacement and orthognathic surgery did not develop in parallel, leading to various combinations of planning for orthognathic surgery and TMJ replacement with the aim of performing both procedures simultaneously in one stage. Nowadays, improvements in virtual planning and three-dimensional printing have allowed these procedures to be conducted in the same surgical step based on fully digital planning and entirely customized surgery. This paper introduces a fully digital protocol for the treatment of end-stage TMJ disease and associated acquired dentofacial deformities, in which all surgical steps are customized and the whole surgery is performed in succession using automated procedures, thanks to the combined use of virtual surgical planning, surgical guides, custom-designed TMJ prostheses, and patient-fitted osteosynthesis devices.